Kudus and Its Sweet Soya Sauces Stories in Mediating Multiculturalism Learning - Kewuel, Hipolitus Kristoforus; Efrizal, Efrizal; Nurmansyah, M. Andhy; Khasanah, Ismatul; Budiyanto, Ary (Institute of Research and Community Service, University of Brawijaya, 2016)
Multicultural reality of Indonesian society has encouraged many conflicts. Many people have tried to create a multicultural atmosphere. The scholars, politicians, and security forces attempted in their respective fields there are theoretical, ideal, and practical. This approach of simple ethnography research at Kudus reveals the unique role of these sweet soya sauces or ketchups. That is, it is not just being a condiment for flavoring the Kudus people dishes, but also already act as multicultural learning media. The good cooperation between the two ethnic groups, the Chinese as the owner of ketchup industries and their Javanese workers, clients, and customers have shown that these Ketchups has become one of the unifying elements that are commonly depicted always in a conflict; andÂ the latest event clashes between Chinese and pribumi at Kudus was in 1984. Thus, by looking at the Ketchups roles, this research shown that the ketchup industries in Kudus have melted the tongue and heart of Kudus people (China-Native) taste in a delicious thickened of ketchup liquid that always served at home, food-stalls, hotels, and restaurants.Keywords: Sweet Soya Sauces , Ketchup,Â Media, Multiculturalism Learning, Kudus